The Effect of Good Corporate Governance and Islamicity Financial Performance Index of Internal Fraud Sharia Banking Period 2014-2017 - Ayu Irmasari Raharjanti; Rais Sani Muharrami (Journal of Business and Management Review, 2020)
This study aims to study the effect of Good corporate governance and the Islamic Financial Performance Index on Internal fraud. The Islamicity Financial Performance Index indicators used are Profit Sharing Ratios, Islamic Income Ratios, Islamic Investment Ratios, and Equitable Distribution Ratios. Using quantitative with secondary data taken from the website of each Islamic Banks (BUS) period 2014-2017. The survey used in this study is a company regristered in the Islamic Banks (BUS) Financial Services Statistics 2017. The total sample is 11 Islamic Banks. The technique of deliver data, while the data analysis technique uses multiple linear regression techniques with SPSS 23. The results of the study indicate that Good corporate governance and Islamic Income Ratio show positivity to internal fraud. While the variable Profit Sharing Ratio, Islamic Investment Ratio, and Equitable Distribution Ratio have no effect on Internal fraud